Hydrobiological aspects of fisheries in small reservoirs in the Sahel region - Baijot, Etienne; Moreau, Jaques; Bouda, Sana (Technical Centre for Agricultural and Rural Cooperation, 1997)
This book discusses the physical and hydrobiological aspects of fisheries, fish communities, the biology of important fish species, traditional and improved fishing practices, and related socio-economic issues in Burkina Faso.